Role of Anopheles baimaii: potential vector of epidemic outbreak in Tripura, North-east India - Nilanju Pran Sarmah; Ipshita Pal Bhowmik; Devojit Kumar Sarma; Chandra Kanta Sharma; Gajendra Kumar Medhi; Pradyumno Kishore Mohapatra; Jagadish Mahanta; Dibya Ranjan Bhattacharyya (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Malaria is one of the foremost public health concerns in north-east India. The state of Tripura, belonging to north-east India recently reported an outbreak of malaria during 2014 with thousands of positive cases and several deaths due to malaria. The epidemic has occurred mainly in the high transmission areas affecting the young population. This study was undertaken to find out the vector species responsible for the outbreak. # Methodology House frequenting female anophelines were collected by using CDC (Centers for Disease Control and Prevention) miniature light traps. Species confirmation of Anopheles (*An.) baimaii* and *An. minimus* and presence of malaria parasite in mosquitoes was done by rDNA based molecular identification method. # Results A rapid entomological survey revealed the involvement of *An. baimaii* on the basis of evidences like high salivary gland infectivity to *P. falciparum* (11%), dominant presence over other anophelines and exclusive anthropophily, detected during the epidemic. # Conclusion This is the first report of incrimination of *An. baimaii* as vector of malaria in Tripura. Encroachment of dense forested areas for shifting cultivation (Jhum) and other activities, suitable environmental condition for vector propagation, and other factors like inadequate vector control and surveillance in remote areas seems to be the probable causes responsible for this epidemic.